The Effect of the Ball Size on the Product Characteristics of Shaker HEBM to Produce Nano Particle from Bamboo Charcoal - Sastrowiyono, Supriyono (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2018)
The objective of this research is to study the effect of ball size on characteristics of product of shaker high energy ball milling (HEBM) to produce nano particle from bamboo charcoal. A new shaker mechanism is developed. The characteristics of the particle are represented by particle size, surface morphology, and the substances presence in the product. Particle size analyzer (PSA) is conducted to have the particle sizes, whereas SEM and EDX are used to have surface morphology and substances presence in the products respectively. The mixtures of 11 gr of bamboo charcoal powder of 200 meshes and about 299 gr of steel ball are placed in vials. The vial is from stainless steel cylinder with 1 inch diameter and 120 mm length. The stroke of the shaker is 54 mm at increasing speed of connecting rod pulley for every 1 million cycles. The total number of cycle is 3 million. Therefore, the connecting rod speed of the first 1 million cycles is 300 rpm, the second is 333 rpm, and the third is 367 rpm. The steel ball sizes are and inch. PSA results indicate that there is no certain correlation between the steel ball size and particle size. The final shape of the particles is determined by fracture mechanism. The highest substance presence in the result is carbon and followed by silicon.